Papan Jam Analog: Media Edukatif Pembelajaran Matematika Madrasah Ibtidaiyah - Linda Indiyarti Putri; Abdul Basir (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2020)
The students' difficulties on understanding the material and the lack of the enthusiasm in learning mathematics, especially in angle measurement material were be the basic reasons for this research. In addition, conventional learning methods that characterized by lectures were still often used by teachers in learning. Therefore, the learning not being more active, effective, and enjoyable. The development of educational learning media like analog clock board was one of the solutions to improve students' understanding. This research aims to determine the effectiveness of analog clock board as learning media to solve mathematics learning problems. The development model used was a 4D development research model. The results of media validation stated that analog clock board was feasible to be used in mathematics learning for angle measurement material. In addition, the results of the questionnaire shown that 90% of teachers and 100% of students stated the media was "very interested". The experiment results showed that analog clock board was more effective to improve students' understanding on angle measurement.